LEGAL AND SOCIOLOGICAL ANALYSIS OF WASTE MANAGEMENT IN ALOR REGENCY FROM THE PERSPECTIVE OF FORMING REGIONAL REGULATIONS - Ferdinandus Ngau Lobo; Maria Imaculata Go'o Laki; Eugenia Soares De Yesus; Gabriel Faustin Vicky Seran; Alessandro Nandito S Wadan (EKSEKUSI, 2026)
ABSTRACT Waste management is a pivotal issue in regional environmental policy, particularly in archipelagic regions such as Alor Regency, which faces limitations in waste management facilities and infrastructure. This study aims to analyze the juridical and sociological aspects of waste management in Alor Regency to serve as the basis for the formation of a Regional Regulation concerning Waste Management. The research method employed is normative juridical with a socio-legal approach, conducted through the analysis of statutory regulations and empirical data obtained from regional agency reports, scientific literature, and observations of waste management conditions. The results indicate that despite a strong legal foundation provided by Law No. 18 of 2008, Government Regulation No. 81 of 2012, Law No. 32 of 2009, and regional autonomy authority under Law No. 23 of 2014, implementation in Alor Regency remains ineffective due to low community participation, inadequate infrastructure, and a weak legal culture. Sociologically, the increasing volume of waste and changes in community consumption behavior are not commensurate with the available waste management capacity. Therefore, the enactment of a Regional Regulation is an urgent necessity to provide legal certainty, strengthen institutional frameworks, and promote a sustainable waste management model based on community participation and the 3R principles.Keywords: Waste management, juridical analysis, sociological analysis, Regional Regulation, Alor Regency. ABSTRAK Pengelolaan sampah merupakan isu sentral dalam kebijakan lingkungan hidup daerah, terutama di wilayah kepulauan seperti Kabupaten Alor yang menghadapi keterbatasan sarana dan prasarana persampahan. Penelitian ini bertujuan menganalisis aspek yuridis dan sosiologis pengelolaan sampah di Kabupaten Alor sebagai dasar pembentukan Peraturan Daerah tentang Pengelolaan Sampah. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan sosiolegal, melalui analisis peraturan perundang-undangan dan data empiris yang diperoleh dari laporan instansi daerah, literatur ilmiah, dan observasi terhadap kondisi pengelolaan sampah. Hasil penelitian menunjukkan bahwa meskipun terdapat dasar hukum yang kuat melalui UU No. 18 Tahun 2008, PP No. 81 Tahun 2012, UU No. 32 Tahun 2009, serta kewenangan otonomi daerah dalam UU No. 23 Tahun 2014, implementasi di Kabupaten Alor masih tidak efektif karena rendahnya partisipasi masyarakat, minimnya infrastruktur, dan lemahnya budaya hukum. Secara sosiologis, meningkatnya volume sampah dan perubahan perilaku konsumsi masyarakat tidak sebanding dengan kapasitas pengelolaan sampah yang tersedia. Oleh karena itu, pembentukan Peraturan Daerah menjadi kebutuhan mendesak untuk memberikan kepastian hukum, memperkuat kelembagaan, serta mendorong model pengelolaan sampah yang berkelanjutan berbasis masyarakat dan prinsip 3RKata.Kunci: Pengelolaan sampah, analisis yuridis, analisis sosiologis, Peraturan Daerah, Kabupaten Alor.